Seasonal optical backscattering in hypersaline waters: In-situ observations and data analysis. - Arwa Najah; Maryam R Al Shehhi (PLoS ONE)
Relationships of backscattering coefficients with the physical and biological properties in hypersaline waters like the Arabian Gulf are poorly studied. They may differ from other non-hypersaline waters which contribute the majority of data used to develop and parameterize optical models. Herein, we analyze the covariation of salinity, temperature, Chlorophyll-a (Chl-a), color dissolved organic matter (CDOM), ammonium, and turbidity with seawater backscattering coefficients bb(λ). This analysis is based on in-situ measurement of total backscattering and satellite total backscattering coefficients retrieved from the Visible Infrared Imaging Radiometer Suite (VIIRS). The in-situ measurements have been collected in the southern region of the Arabian Gulf waters, characterized by salinity and high evaporation rate. The results showed that turbidity is the main contributor to the increase in bb (λ) which could reach up to 77%. In addition, an increase in salinity is associated with an increase in the bb (λ) up to 19% especially at 532 nm. As for the temperature, we found that bb(λ) during the winter season is higher than in the summer season which could be due to the mixed effect of the surface sedimentation and the well-mixed column during winter. As for the Chl-a, there is a noticeable covariation between bb (λ) and the Chl-a concentration. Thus, we examined the probability distribution of Chl-a against different ranges of bb(λ) and found that Chl-a can follow log-normal and Weibull probability distribution which can be used for different bb(λ) ranges of 532 and 488 nm. Based on this study, we found that the hypersaline waters of the Gulf have bb scattering patterns that are consistent with the previously reported studies elsewhere.